Cobalamin Levels in Fish and Fortified Milk Substitutes - Motta, Carla (2021)
Objectives: Natural forms of vitamin B12, methylcobalamin (MeCbl),andhydroxocobalamin(OHCbl)arebioidenticaltotheforms occurringinhumanphysiologyandanimalfoods.However,infortified foods, different vitamers can be present including cyanocobalamin (CNCbl), a synthetic form that can be problematic due to cyanide content.Themaingoalofthisworkistoidentifythedifferentvitamin B12 vitamers (CNCbl, MeCbl, and OHCbl) in fish and in fortified soy milktocharacterizethedifferenttypesofcobalaminspresentinnatural andfortifiedfoods. Methods: Samples of a fish from the Portuguese water coastline (mackerel) and samples of commercial fortified soy milk beverages available on the Portuguese market were collected. Mackerel samples were analyzed raw, after boiling on steam and canned in water. The clean-up was performed by immunoaffinity columns. The different vitamerswereanalyzedinaUHPLCcoupledtoatriplequadrupolemass spectrometerwithelectrosprayionization. Results: In mackerel, the identified vitamers were MeCbl (prevalent form) and OHCbl. The sum of vitamers is in raw fish was 9.2±1.2 µg/100 g, in steamed fish, 8.3±0.6 µg/100 g and in canned fish6,1±0,8µg/100g.Insoymilk,theidentifiedvitamerwasCNCbl, with values between 0.23±0.2 µg/100 mL and 0.75±.3 µg/100 mL. Taking into account the adequate intake for adults (4µ/day), the consumption of 100 g of mackerel represents from 61% (in canned fish) to 97% (in raw fish) of the recommendations. Regarding the soy milk, we observe that values found analytically, are different from the ones reported in the label (0.38 µg/100 mL). Fortified soy milky presents in Portugal a medium consumption of 224 mL/day, in consumers (IAN-AF, 2016). For this population, the consumption of soymilkrepresentsamaximumof44%oftherecommendedadequate intake. Conclusions: Mackerel represents an important source of natural cobalamins,withrecognizedbioavailabilitiesandphysiologicaleffects. Individuals or ethnic groups whose diets exclude or restrict animalbased diets (such as vegans) may be at risk for inadequate nutrient intake.